Adaptation and tolerance mechanism of sesame to drought stress: Adaptation and tolerance mechanism of sesame to drought stress - P RATNAKUMAR,; BRIJ B PANDEY,; GOPIAK K,; SRAVANTHI A,; SONIA E,; GS LAKSHMI,; K KUSUMA,; MANIKANTA Ch L N,; LORA P ANUSHA,; K RAMESH,; KT RAMYA,; Y PRADUMAN,; et al. (Journal of Oilseeds Research, 2023)
Drought, seasonal temperature variations affects yield of sesame (Sesamum indicum L.) Under rainfed conditions. Sesame germplasm were assessed for drought tolerance across season in field conditions. Seed yield was significantly and positively associated with functional root traits, leaf potassium, leaf tissue moisture and CT across seasons. The identified trait, and specific germplasm will be used further in crop improvement programme.